Preparation method and application of nano-enzyme hydrogel dressing
By integrating manganese and zinc ion-doped MOF-based nanoenzyme Mn-ZIF@GOx in bacterial cellulose hydrogels, the problem of difficulty in healing in diabetic wounds is solved, and anti-inflammatory, reactive oxygen scavenging, antibacterial and angiogenesis is achieved. Multifunctional effect, significantly promoting diabetic wound healing.
Patent Information
- Application Number
- CN202411143421.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-01-03
AI Technical Summary
Due to excessive accumulation of reactive oxygen species, persistent inflammation and bacterial infection in patients with diabetes, existing treatment methods cannot effectively solve the problems related to ROS dysregulation, and lack treatment strategies that can simultaneously sterilize, anti-inflammatory, reduce ROS and promote angiogenesis.
Develop a nanoenzyme hydrogel dressing to simulate ultrasonic by integrating manganese and zinc ion-doped metal-organic framework (MOF)-based nanoenzyme Mn-ZIF@glucose oxidase (GOx) in bacterial cellulose hydrogels The activity of oxide dismutase and catalase reduces local pH, eliminates reactive oxygen species, and promotes angiogenesis.
It realizes the multifunctional effect of integrating anti-inflammatory, reactive oxygen scavenging, antibacterial and angiogenesis, significantly promotes diabetic wound healing, reduces inflammatory response, increases angiogenesis, improves wound contraction and skin regeneration speed, has good biocompatibility and low cost.
Smart Images

Figure CN119236155A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wound repair materials, and specifically relates to a preparation method and application of a nanoenzyme hydrogel dressing. Background Art
[0002] The wounds of diabetic patients are often seriously affected by excessive accumulation of reactive oxygen species (ROS), persistent inflammation, hypoxia and bacterial infection, which hinder wound healing. At present, the treatment methods for diabetic wounds include debridement and antibiotic treatment, which have antibacterial effects to a certain extent, but cannot solve the pathological problems related to ROS dysregulation. Therefore, it is very promising to develop a therapeutic strategy that can simultaneously kill bacteria, fight inflammation, reduce local ROS and promote angiogenesis. This comprehensive treatment method is expected to improve wound healing in diabetic patients and provide a more effective treatment plan.
[0003] At present, nanozyme materials with enzyme-like catalytic properties have made significant progress. Nanozymes can be transformed into natural antioxidant enzymes that can remove a variety of active substances. Compared with traditional small molecule antioxidants and natural enzymes, nanozymes not only have the effect of eliminating ROS, but also have obvious advantages such as low cost, strong stability, and good biocompatibility.
[0004] Metal-organic frameworks (MOFs) exhibit structured coordination networks formed by organic linkers connected to metal-containing nodes with well-defined and customizable voids and channels, providing a hydrophobic coordination environment similar to that of natural enzymes. In addition, the catalytic properties and structures of MOFs can be tailored by selecting appropriate metal ions and ligands, which shows the multifunctional potential of MOFs in developing nanozymes with the ability to scavenge ROS and promote angiogenesis.
[0005] Bacterial cellulose (BC) hydrogel has good bioadhesive properties and can effectively adhere to the wound surface to form a protective layer. In addition, it has the ability to regulate water content, allowing it to absorb wound secretions to a certain extent, keep the wound clean, and provide an appropriate moist environment. However, as a carrier, pure bacterial cellulose hydrogel has limited effect in promoting the healing of diabetic wounds and lacks the ability to effectively regulate environmental factors for targeted treatment and repair. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of nanozyme hydrogel dressing. The bacterial cellulose hydrogel loaded with nanozymes can fully utilize the advantages of bacterial cellulose hydrogel and the characteristics of MOF-based nanozymes to accurately regulate the wound environment, thereby achieving more efficient treatment of diabetic wounds. x) were assembled on MOF doped with Mn and Zn ions to construct a new MOF-based nanozyme Mn-ZIF@GO x Then the prepared Mn-ZIF@GO x Integrated in BC hydrogel (Mn-ZIF@GO x / BC, MZGB).
[0007] The present invention proposes to dope MOF with manganese and zinc ions and combine it with GO x The MZGB hydrogel combines the advantages of nanozymes and natural enzymes, and utilizes the abundant glucose in the body, GO x The hydrogel oxidizes glucose into gluconic acid, thereby reducing the pH value of the local wound; the hydrogel converts O 2 •− Convert to O 2 and H 2 O 2 , by simulating the activity of catalase (CAT), endogenous and exogenous H 2 O 2 Decompose into O 2 , reduce oxidative stress, relieve hypoxia, and promote healing of diabetic wounds.
[0008] The present invention adopts the following technical solution: A method for preparing a nanoenzyme hydrogel dressing comprises the following steps: Step 1: Synthesis of Mn and Zn doped MOF: Dissolve dimethylimidazole in methanol, ultrasonicate for 10-20 min, and then add Zn(CH 3 COO 2 •2H 2 O and Mn(NO 3 ) 2 •4H 2 O was dissolved in the second methanol and ultrasonically treated for 20-30 min. The stirred dimethylimidazole solution and Zn(CH 3 COO 2 •2H 2 O and Mn(NO 3 ) 2 •4H 2 O mixed solution was mixed at room temperature, stirred continuously for 5 h, centrifuged, and the obtained product was washed with methanol and then dried to obtain Mn and Zn doped MOF, which was recorded as Mn-ZIF; Step 2: Mn-ZIF@GO x Synthesis: Weigh Mn-ZIF and dissolve it in deionized water, add GO x, stirred at 30 ° C for 24 hours, after the reaction was completed, centrifuged, the precipitate was washed with deionized water for several times, and vacuum dried to obtain Mn-ZIF@GO x ; Step 3, preparation of bacterial cellulose BC: Acetobacter xylinum was initially inoculated into the culture medium at 30°C and an oscillation speed of 200 rpm, and incubated for 24 hours to allow the bacteria to proliferate. The proliferated culture medium was transferred to the fermentation broth, and then the mixture was placed in a constant temperature shake box for 12 hours. The fermented broth was poured into a shallow tray and returned to the constant temperature shake bottle. A BC membrane could be harvested every 12-24 hours. The BC membrane was continuously washed with deionized water for 48 hours, and then boiled in 0.1M NaOH for 1 hour to remove impurities. Finally, the BC was rinsed with deionized water until the solution became neutral, completing the purification process. Step 4: Mn-ZIF@GO x Preparation of BC hydrogel: BC was dispersed in deionized water and then Mn-ZIF@GO was added x , and continuously shaken at 160 rpm and 30 °C for 24 h to ensure that Mn-ZIF@GO x Dispersed evenly in BC hydrogel, Mn-ZIF@GO was finally obtained. x / BC hydrogel, denoted as MZGB.
[0009] Furthermore, the ratio of the dimethylimidazole to the first methanol in the first step is 3.2-3.3 g:40 mL; Zn(CH 3 COO 2 •2H 2 O、Mn(NO 3 ) 2 •4H 2 The usage ratio of O and the second methanol is 0.8-0.9 g:0.2 g:20 mL.
[0010] Furthermore, in the second step, the Mn-ZIF, deionized water, GO x The dosage ratio is 0.8-1g:20-30mL:40-50mg.
[0011] Furthermore, the components of the culture medium in the third step include: 20 g / L glucose, 6 g / L ammonium sulfate, 1 g / L potassium dihydrogen phosphate, 0.4 g / L magnesium sulfate, 3 g / L peptone, 2.25 g / L yeast extract powder, 0.4 g / L sodium carboxymethyl cellulose, and the solvent is 100 mL water.
[0012] Furthermore, the components of the fermentation broth in the third step include: 22.5 g / L glucose, 27.5 g / L sucrose, 0.2 g / L calcium lactate, 0.6 g / L citric acid, 7.5 g / L yeast extract, 0.4 g / L sodium carboxymethyl cellulose and 1.5 mL acetic acid.
[0013] Furthermore, in the fourth step, BC, deionized water, Mn-ZIF@GO x The dosage ratio is 1g:20-30mL:100-200mg.
[0014] A nanozyme hydrogel dressing is applied to diabetic wounds for anti-inflammation, reactive oxygen species scavenging, antibacterial and angiogenesis.
[0015] The beneficial effects of the present invention are as follows: 1. The method for preparing the nanozyme hydrogel dressing integrating anti-inflammatory, active oxygen scavenging, antibacterial and angiogenesis functions of the present invention has a wide range of materials and reagents, low cost, and low requirements on equipment and conditions.
[0016] 2. The MZGB hydrogel provided by the present invention comprises Mn-ZIF@GO x Nanozymes are integrated into BC hydrogels to form multifunctional nanotherapeutic materials. MZGB has a significant ability to lower blood sugar levels by utilizing the abundant glucose in the body. x It oxidizes glucose into gluconic acid, thereby reducing the pH value of the local wound; MZGB effectively removes •OH, O by simulating the cascade process of SOD and CAT. 2 •− and H 2 O 2 , while providing oxygen.
[0017] 3. The MZGB hydrogel provided by the present invention can absorb wound tissue fluid and quickly discharge it, preventing wound fluid retention and creating a moist environment for the wound.
[0018] 4. The MZGB hydrogel provided by the present invention has good biocompatibility, no cytotoxicity, and antioxidant properties, which can reduce the damage of ROS in the wound site, reduce the inflammatory response in diabetic wounds, promote angiogenesis and wound contraction, accelerate skin regeneration, and accelerate wound healing.
[0019] 5. The MZGB hydrogel provided by the present invention exhibits antibacterial properties that are independent of ROS. In an acidic system, Mn-ZIF@GO x Dissociation occurs by coordination decomposition, Zn 2+ Shows strong antibacterial function.
[0020] 6. The present invention found in cell experiments that MZGB hydrogel induces M2 macrophage polarization, thereby reducing inflammation; in addition, MZGB creates a good immune microenvironment by reprogramming macrophages, and significantly promotes the proliferation, migration and angiogenesis of fibroblasts and endothelial cells through a paracrine mechanism.
[0021] 7. The in vivo study of the full-thickness skin defect model in diabetic rats found that MZGB hydrogel scavenged ROS, regulated macrophage polarization, modulated the inflammatory microenvironment, and promoted angiogenesis, thereby promoting diabetic wound repair and skin regeneration.
[0022] 8. The MZGB hydrogel provided by the present invention integrates anti-inflammatory, active oxygen scavenging, antibacterial and angiogenesis, which can simultaneously solve the problems of excessive inflammation of diabetic wounds and difficulty in wound healing, promote angiogenesis and wound contraction of diabetic wounds, and accelerate wound healing. It has great potential in the treatment of diabetic wounds.
[0023] 9. The present invention can simultaneously solve multiple problems that cause diabetic wounds to be difficult to heal, and promote wound healing while regulating the wound microenvironment, so as to achieve the purpose of efficiently and quickly treating diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 forMn-ZIF@GO x Schematic diagram of the synthesis of Figure 2 forMn-ZIF@GO x SEM images of Figure 3 For ZIF-8 and Mn-ZIF@GO x XPS spectrum of Figure 4 High-resolution XPS spectra of Zn 2p, Mn 2p, and S 2p; Figure 5 Mn-ZIF and Mn-ZIF@GO x FTIR spectrum of Figure 6 Mn-ZIF and Mn-ZIF@GO x TGA curve of Figure 7 ZIF-8, Mn-ZIF and Mn-ZIF@GO x Zeta potential diagram; Figure 8 Mn-ZIF and Mn-ZIF@GO x XRD spectrum of Fig. 9 forMn-ZIF@GO xSchematic diagram of enzyme-like activity; Fig.10 NADH-mPMS-NBT method for detecting Mn-ZIF@GO x SOD-like activity diagram; Fig.11 Different concentrations of Mn-ZIF@GO x Catalytic H 2 O 2 Generate O 2 Quantity change diagram; Fig.12 Mn-ZIF@GO at different concentrations x ESR spectrum of DMPO / •OH.
[0025] Fig.13 Schematic diagram of the synthesis of MZGB hydrogel; Fig.14 is the SEM image of BC; Fig.15 is the SEM image of MZGB; Fig.16 XRD spectra of BC and MZGB; Fig.17 FTIR spectra of BC and MZGB; Fig.18 Water contact angle images of BC and MZGB; Fig.19 This is the adhesion diagram of MZGB hydrogel; Fig. 20 The results are shown for HUVECs, L929 cells, and RAW264.7 cells after co-culture with different hydrogels for 24 hours; Fig.21 The biosafety performance diagram of the hydrogel was evaluated by hemolysis test; Fig. 22 This is the H&E staining image of MZGB hydrogel used for organs; Fig.23 To evaluate the antibacterial properties of MZGB by plate colony counts and live / dead bacterial staining; Fig.24 To calculate the survival rate of Staphylococcus aureus and Escherichia coli by plate colony counting; Fig.25 Schematic diagram of the establishment of diabetic rat model, wound formation and subsequent healing steps; Fig.26 Representative images showing wound healing in different groups and a schematic diagram of the wound healing process for diabetic rats; Fig. 27 is the wound healing rate of each group at each time point; Fig.28DHE fluorescence images and corresponding fluorescence intensity quantification; Fig.29 Representative H&E and Masson trichrome staining images of wound samples from different groups on days 7 and 14; Fig.30 Representative CD31 immunofluorescence images and relative quantitative analysis are shown; Fig.31 Representative iNOS / CD163 immunofluorescence images and relative quantitative analysis in wound tissues on days 3 and 7; Fig.32 Representative immunofluorescence images and relative quantitative analysis of TNF-α and IL-10 in wound tissues on the 7th day. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0027] Preparation of MZGB hydrogel (1) Mn-ZIF@GO x Preparation of nanozymes: 0.8 g Zn(CH 3 COO 2 •2H 2 O and Mn(NO 3 ) 2 •4H 2 O was dissolved in 20 ml of methanol and stirred evenly with a magnetic stirrer. The mixture was added to 40 ml of 3.2 g of 2-methylimidazole methanol solution and stirred with a magnetic stirrer for 5 hours. The mixture was centrifuged at 12,000 rpm for 10 minutes, washed with methanol three times, and dried under vacuum to obtain Mn-ZIF. 0.8 g of Mn-ZIF was weighed and dissolved in 20 ml of deionized water. 50 mg of GO was added. x , stirred for 24 hours, and after the reaction was completed, centrifuged, the precipitate was washed with deionized water for several times, and vacuum dried to obtain Mn-ZIF@GO x .
[0028] (2) Preparation of MZGB: Under constant temperature shaking conditions (30°C, 200 rpm), Acetobacter xylinumNUST4 was initially inoculated into the culture medium and incubated for 24 hours to allow the bacteria to proliferate. The proliferated culture medium was transferred to a fermentation broth containing 22.5 g / L glucose, 27.5 g / L sucrose, 0.2 g / L calcium lactate, 0.6 g / L citric acid, 7.5 g / L yeast extract, 0.4 g / L sodium carboxymethyl cellulose, and 1.5 mL acetic acid, and the mixture was then placed in a constant temperature shaker for 12 hours. The fermented broth was poured into a shallow tray and returned to the constant temperature shaker. A BC membrane could be harvested every 12-24 hours. The BC was washed continuously with deionized water for 48 hours, then boiled in 0.1M NaOH for 1 hour to remove impurities, and finally rinsed with deionized water until the solution became neutral, completing the purification process.
[0029] To prepare MZGB1, 1 g BC was dispersed in 20 ml deionized water, and then 5 mL Mn-ZIF@GO was added. x (20 mg / mL) and continuously shaken at 160 rpm and 30 °C for 24 h to ensure that Mn-ZIF@GO x The BC and Mn-ZIF@GO were uniformly dispersed in the BC hydrogel, and finally, the hydrogel was rinsed with deionized water. x (40 mg / mL) to synthesize MZGB2, using BC and Mn-ZIF@GO x (80 mg / mL) to synthesize MZGB3, and the other steps were the same as those used for MZGB1.
[0030] Scanning electron microscopy (SEM) was used for morphological evaluation; dynamic light scattering (DLS) was used to determine the particle size distribution; X-ray photoelectron spectroscopy (XPS) was used to determine the elemental composition and chemical state of the samples; Fourier transform infrared spectroscopy (FTIR) was used to identify functional groups; thermogravimetric analysis (TGA) was used to evaluate thermal stability; X-ray diffraction (XRD) revealed structural details; Zeta potential measurements were used to analyze surface charge; and contact angle measurements were used to measure surface wettability.
[0031] like Figure 1 As shown in Figure 2, Mn-ZIF@GO was synthesized by a one-pot method. x ,like Figure 2 As shown in Figure 2, the surface of Mn-ZIF exhibits a rough surface and fuzzy rhombus morphology, indicating that GO exists on the surface of Mn-ZIF. x Layer. Figure 3 and Figure 4 As shown, for Mn-ZIF@GO x The XPS results were evaluated and the characteristic peaks of Zn 2p, Mn 2p, N 1s, O 1s, C 1s, and S 2p were observed. Figure 5 As shown, compared with Mn-ZIF@GO xand FTIR of Mn-ZIF, 1582 cm −1 The peak at further confirmed that GO x Incorporation of Figure 6 As shown in the TGA curve, Mn-ZIF@GO x The weight of Mn-ZIF gradually decreased by about 8.9%, which corresponds to the evaporation of water and other small organic molecules in the MOF cavity. After further heating, Mn-ZIF decomposed in the second stage and lost about 36.66% of its weight. In the same temperature range, due to the evaporation of water and other small organic molecules in the MOF cavity, the weight of Mn-ZIF decreased by about 8.9%, which corresponds to the evaporation of water and other small organic molecules in the MOF cavity. After further heating, Mn-ZIF decomposed in the second stage and lost about 36.66% of its weight. x Decomposition of Mn-ZIF@GO x The weight loss is about 49.84%. x After loading onto Mn-ZIF, it was observed to shift toward negative charge. These results further validated the Mn-ZIF@GO x Synthesis of Figure 8 As shown, compared with the XRD of Mn-ZIF, Mn-ZIF@GO x The peak of GO x The incorporation of did not affect the crystal structure, which ensured the preservation of the internal protein biological activity.
[0032] In the present invention, Mn-ZIF@GO x Nanozymes are combined with BC hydrogel to form MZGB multifunctional composite hydrogel. SEM depicts the three-dimensional network structure of pure BC, which is conducive to the entry of nanoparticles into its cavity. x After functionalization of BC with nanoparticles, the deposition of nanoparticles on or around the nanofibers was observed. The crystal characteristics of BC and MZGB were analyzed by XRD. The diffraction peaks in the XRD spectrum of BC correspond to the (110) and (200) crystal planes of the MZGB composite, indicating that the crystal properties of BC and MZGB remain unchanged after the composite is formed. The FTIR spectrum of MZGB at 1566 cm -1 、1421 cm -1 、993 cm -1 and 1308cm -1 The characteristic peaks are attributed to C=N stretching, CN stretching and imidazole bending vibration. These results show that Mn-ZIF@GO x The hydrophilicity of the material is a key feature for cell adhesion and can be evaluated by contact angle measurements. Hydrogels used to treat diabetic skin defects require excellent adhesion properties. MZGB can be well attached to the model finger and can be rotated without falling off, indicating strong adhesion.
[0033] Active oxygen scavenging ability The NADH-mPMS-NBT system was used to measure SOD-like activity. 936 μM NADH solution, 336 μM mPMS solution and 120 μM NBT solution were prepared, 200 μL NADH and 200 μL mPMS solution were taken respectively, and then Mn-ZIF@GO was added. x Finally, 20 μL of NBT solution was added for color development, and the absorbance of the solution at 560 nm was measured using a UV spectrophotometer.
[0034] The CAT-like activity was evaluated by measuring the oxygen content in the buffer solution. x Add to the H 2 O 2 The mixed solution was added with Tris-HCl buffer solution (0.1 M, pH 7.2) (20 mM), and the oxygen content in the mixed solution was measured using a dissolved oxygen meter.
[0035] Electron spin resonance (ESR) technology was used to further verify the Mn-ZIF@GO x First, FeSO 4 (1.8 mM) and H 2 O 2 (5mM) was used for Fenton reaction to generate ·OH and the reaction lasted for 10 minutes. Then Mn-ZIF@GO x It was added to the free radical system, with DMPO as the spin trapping agent, and combined with OH to form a spin adduct, and the ESR spectrum with an intensity ratio of 1:2:2:1 was analyzed.
[0036] Evaluation of Mn-ZIF@GO using the NADH-mPMS-NBT system x In this system, NADH reacts with mPMS to produce a large amount of O 2 •- , O 2 •- Oxidation of NBT produces a characteristic UV absorption peak at 560 nm. Adding Mn-ZIF@GO to the NADH-mPMS-NBT system x The absorption peak at 560 nm was significantly reduced, indicating that Mn-ZIF@GO x With clear O 2 •- Mn-ZIF@GO x was added to a solution containing H 2 O 2 The dissolved oxygen level was measured by a dissolved oxygen monitor in a buffer solution. It was found that the addition of Mn-ZIF@GO x After that, the oxygen level continued to increase.x The increase in concentration, H 2 O 2 The decomposition rate was accelerated and the dissolved oxygen level was significantly increased. ESR was used to further verify that Mn-ZIF@GO x The ability to scavenge •OH, the ESR spectrum shows four characteristic peaks with an intensity ratio of 1:2:2:1, which are typical characteristic peaks of the spin adducts formed by the reaction of DMPO and •OH, and the signal intensity is related to the •OH concentration. x After that, the DMPO / •OH signal was significantly weakened, indicating that Mn-ZIF@GO x It has effective scavenging ability for •OH.
[0037] Biosafety Determination Cytotoxicity was assessed using the Cell Counting Kit-8 (CCK-8): Human umbilical vein endothelial cells (HUVECs), L929 mouse fibroblast cell line (L929 cells), and RAW264.7 mouse monocyte / macrophage cell line (RAW264.7 cells) were cultured at 5.0 × 10 3 The cells were seeded in a 96-well plate at a density of 1 μg / mL and incubated for 24 hours. The cells were then treated with BC and MZGB hydrogels at a concentration of 1 μg / mL and incubated for another 24 hours at 37°C. 10 μL of CCK-8 working solution was added to each well and incubated for another 2 hours. Cell viability was measured using a microplate reader with an absorbance of 450 nm, and the optical density values were normalized to the PBS control.
[0038] Hemolysis test: 500 μL of SD rat blood was taken and centrifuged at 3500 rpm for 5 minutes at 4°C. The supernatant was removed, and the red blood cells were washed three times and resuspended in 5 ml PBS. Subsequently, 250 mg of hydrogel sample was mixed with 1 mL of red blood cell suspension in a test tube and incubated at room temperature for 4 hours. The experiment used negative control (PBS) and positive control (water) samples to calculate the degree of hemolysis. After incubation, all samples were centrifuged at 3500 rpm for 5 minutes, and the absorbance of the supernatant was measured at 545 nm using an enzyme reader.
[0039] The results of CCK-8 experiments showed that MZGB had good biocompatibility and had little effect on the activity of HUVECs, L929 cells, and RAW264.7 cells. The safety and applicability of the material were evaluated by hemolysis experiments to ensure that it would not cause serious toxicity or adverse reactions when used in vivo. In addition, the biosafety of MZGB was evaluated by H&E staining of major organs (heart, liver, spleen, lung, and kidney), and no obvious histological abnormalities were observed in these tissues, indicating that MZGB had good biocompatibility.
[0040] Antibacterial properties of MZGB To evaluate the antibacterial properties of MZGB using the agar plate count method, 1 mL of Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ) suspension (concentration of 1×10 7 CFU / mL) were incubated with BC and MZGB at 37°C for 24 h. 100 μL of bacterial suspension was spread on agar plates and cultured at 37°C for 24 h. The colonies were counted and the relative survival rate was calculated.
[0041] Bacterial viability was assessed using a live / dead bacterial staining kit (SYTO9-PI). Bacterial cultures were stained with PI and SYTO-9 dye at a concentration of 10 μg / mL for 20 min, and after washing with PBS, the bacteria were suspended in PBS, spotted on a slide, and observed using a laser confocal microscope.
[0042] In the in vitro bacterial assay, different concentrations of bacterial suspensions were applied to the control, BC, and MZGB samples, and the bacteria were collected from the cellulose using PBS buffer solution (pH = 7.4), and their viability was assessed using plate counts and live / dead staining. S. aureus and E. coli The number of β-cells decreased significantly in a concentration-dependent manner. After treatment with MZGB1, MZGB2 and MZGB3, S. aureus The relative survival rates were 33.67%, 14.44%, and 8.64% respectively; E. coli The relative survival rates of the control group, BC group and MZGB group were 37.75%, 12.38% and 4.86%, respectively. Bacterial live / dead staining showed that almost all bacteria in the control group and BC group were stained green. S. aureus and E. coli The green fluorescence of SYTO-9 decreased, while the red fluorescence of PI increased in a concentration-dependent manner.
[0043] Evaluation of wound healing ability in diabetic rats To evaluate the in vivo therapeutic effect of MZGB hydrogel, a diabetic wound model was established. SD rats were first fed a high-fat, high-sugar diet for 8 weeks, followed by a single intraperitoneal injection of streptozotocin (35 mg / kg) to induce diabetes in male SD rats. Blood glucose and body weight of the rats were measured every day for 7 consecutive days. Rats with random blood glucose levels exceeding 16.7 mmol / L, accompanied by weight loss and polyuria, were considered to have successfully established diabetes.
[0044] SD rats were anesthetized with sodium pentobarbital (50 mg / kg) and the dorsal hair was shaved. A full-thickness skin wound with a diameter of 10 mm was formed on the back using a circular punch. The rats were then randomly divided into 4 groups: normal group, diabetes (DM) group, BC group, and MZGB group. Digital images of the wounds were taken on days 4, 7, 10, and 14 after treatment, and the wound healing rate was analyzed using ImageJ software.
[0045] The results showed that the overall trends of wound healing in the four groups were similar, but the healing rates were significantly different. Quantifying the wound healing rate, on the 7th day, the wound healing rate of the MZGB hydrogel-treated group was 63.48%, significantly higher than that of the other groups. The healing rate of the DM group was only 25.29%, significantly lower than that of the normal group (41.7%). Purulent exudate was visible on the wound surface of the DM group. After 10 days of treatment, the wound area of each group was further reduced. Compared with the other groups, the healing rate of the MZGB group was significantly higher, while the DM group still had a large amount of unhealed wound area. In addition, the wound tissue treated with MZGB hydrogel had a higher hair coverage rate, and the new skin tissue was very similar to the adjacent normal skin, indicating better wound healing performance relative to other groups.
[0046] Skin wound tissues were collected and fixed with 4% paraformaldehyde for 24 h. After fixation, the tissues were dehydrated, embedded, and sliced for histological observation. H&E staining and Masson's trichrome staining were used to evaluate the pathological state and healing of the wounds on days 7 and 14. H&E staining showed that the DM group had obvious inflammatory areas and incomplete epithelial layers on day 7. In contrast, the wound tissues treated with MZGB showed a thicker layer of regenerated granulation tissue. On day 14, the epithelial tissue in the MZGB group was intact and continuous, and re-epithelialization was most significant. In addition, newly formed sebaceous glands and hair follicles were observed, similar to normal skin tissue. Masson's staining results showed that the wounds had the highest collagen content after MZGB treatment, the collagen fiber density increased significantly, and the skin appendage regeneration was obvious. The collagen fibers in the MZGB group showed a more regular topological structure and collagen network arrangement. In contrast, the fiber arrangement in the other groups was relatively loose and underdeveloped.
[0047] On day 4, ROS levels in frozen sections were detected using a dihydroethidium (DHE) fluorescent probe. On days 3 and 7, the polarization of CD163 (M2 macrophages) and iNOS (M1 macrophages) was detected by immunofluorescence staining. On day 7, inflammation and angiogenesis in damaged skin tissues were detected by immunofluorescence staining, and TNF-α, IL-10, and CD31 were detected, and the fluorescence intensity was quantitatively analyzed using ImageJ software.
[0048] The DHE probe was used to detect the level of reactive oxygen species in the wound. Bright red fluorescence signals appeared in the DM group, indicating that the level of ROS was high. In contrast, the red fluorescence in the MZGB group was significantly reduced. Quantitative analysis further confirmed that the level of ROS in the MZGB group was lower than that in the DM group, indicating that MZGB can effectively remove excess ROS and relieve oxidative stress.
[0049] Immunofluorescence staining was used to investigate the infiltration of macrophages in the wounds. The levels of iNOS-labeled M1 macrophages were significantly higher in the DM and BC groups compared with the other groups. In contrast, the MZGB group had significantly fewer iNOS-expressing M1 macrophages and a higher presence of CD163-labeled M2 macrophages. α Compared with the Normal, DM and BC groups, the expression level of TNF- α These results indicate that MZGB can effectively promote the polarization of macrophages to the M2 phenotype, thereby producing a good therapeutic effect on diabetic inflammatory wounds.
[0050] The level of angiogenesis was assessed by immunofluorescence staining of the endothelial-specific marker CD31. MZGB significantly promoted the expression of CD31, and significant angiogenesis was observed in the MZGB group. This finding suggests that MZGB is very effective in initiating new blood vessel growth. Therefore, MZGB hydrogel accelerates angiogenesis in diabetic wounds and further promotes the healing process in vivo.
[0051] The MZGB hydrogel system developed by the present invention exhibits good adhesion in vitro, and the loaded nanozymes quickly consume glucose in the microenvironment, while exhibiting activities similar to SOD and CAT, thereby producing superior ROS scavenging ability. In addition, we found that the MZGB hydrogel has antibacterial properties that are independent of ROS. In vivo experiments have shown that the MZGB hydrogel can effectively remove ROS and regulate the inflammatory microenvironment through macrophage reprogramming, thereby promoting wound angiogenesis and promoting diabetic wound healing. Therefore, the MZGB hydrogel has outstanding efficacy in promoting diabetic wound healing and has important potential in the treatment of immune regulation-related wounds.
[0052] The above description is a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanoenzyme hydrogel dressing, characterized in that: The steps include: Step 1, synthesis of Mn and Zn doped MOF: dissolve dimethylimidazole in the first methanol, ultrasonically treat for 10-20 min, then dissolve Zn(CH3COO)2•2H2O and Mn(NO3)2•4H2O in the second methanol in proportion, ultrasonically treat for 20-30 min, mix the stirred dimethylimidazole solution and the mixed solution of Zn(CH3COO)2•2H2O and Mn(NO3)2•4H2O at room temperature, stir continuously for 5 h, centrifuge, wash the obtained product with methanol, and then dry to obtain Mn and Zn doped MOF, recorded as Mn-ZIF; Step 2: Mn-ZIF@GO x Synthesis: Weigh Mn-ZIF and dissolve it in deionized water, add GO x , stirred at 30 ° C for 24 hours, after the reaction was completed, centrifuged, the precipitate was washed with deionized water for several times, and vacuum dried to obtain Mn-ZIF@GO x ; Step 3, preparation of bacterial cellulose BC: Acetobacter xylinum was initially inoculated into the culture medium at 30°C and an oscillation speed of 200 rpm, and incubated for 24 hours to allow the bacteria to proliferate. The proliferated culture medium was transferred to the fermentation broth, and then the mixture was placed in a constant temperature shake box for 12 hours. The fermented broth was poured into a shallow tray and returned to the constant temperature shake bottle. A BC membrane could be harvested every 12-24 hours. The BC membrane was continuously washed with deionized water for 48 hours, and then boiled in 0.1M NaOH for 1 hour to remove impurities. Finally, the BC was rinsed with deionized water until the solution became neutral, completing the purification process. Step 4: Mn-ZIF@GO x Preparation of BC hydrogel: BC was dispersed in deionized water and then Mn-ZIF@GO was added x , and continuously shaken at 160 rpm and 30 °C for 24 h to ensure that Mn-ZIF@GO x Dispersed evenly in BC hydrogel, Mn-ZIF@GO was finally obtained. x / BC hydrogel, denoted as MZGB.
2. The method for preparing a nanoenzyme hydrogel dressing according to claim 1, characterized in that: In the first step, the usage ratio of dimethylimidazole to the first methanol is 3.2-3.3 g:40 mL; the usage ratio of Zn(CH3COO)2•2H2O, Mn(NO3)2•4H2O and the second methanol is 0.8-0.9 g:0.2 g:20 mL.
3. The method for preparing a nanoenzyme hydrogel dressing according to claim 1, characterized in that: In the second step, Mn-ZIF, deionized water, GO x The dosage ratio is 0.8-1g:20-30mL:40-50mg.
4. The method for preparing a nanoenzyme hydrogel dressing according to claim 1, characterized in that: The components of the culture medium in the third step include: 20 g / L glucose, 6 g / L ammonium sulfate, 1 g / L potassium dihydrogen phosphate, 0.4 g / L magnesium sulfate, 3 g / L peptone, 2.25 g / L yeast extract powder, 0.4 g / L sodium carboxymethyl cellulose, and the solvent is 100 mL water.
5. The method for preparing a nanoenzyme hydrogel dressing according to claim 1, characterized in that: The components of the fermentation broth in the third step include: 22.5 g / L glucose, 27.5 g / L sucrose, 0.2 g / L calcium lactate, 0.6 g / L citric acid, 7.5 g / L yeast extract, 0.4 g / L sodium carboxymethyl cellulose and 1.5 mL acetic acid.
6. The method for preparing a nanoenzyme hydrogel dressing according to claim 1, characterized in that: In the fourth step, BC, deionized water, Mn-ZIF@GO x The dosage ratio is 1g:20-30mL:100-200mg.
7. A nanozyme hydrogel dressing prepared by the preparation method of claim 1 is used for anti-inflammation, active oxygen scavenging, antibacterial and angiogenesis of diabetic wounds.
Citation Information
Cited By
Blood glucose response type hydrogel
CN120983700A